DETERMINATION OF GLUCOSE WITH THE HELP OF GLUCOSE OXIDASE AND CATALASE: UDC: 543.8:543.9 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The conditions of the enzymatic determination of glucose with the help of glucose oxidase were optimized. The oxidation ofbrompуrogallol red by hydrogen peroxide with the help of catalase was used as indicator reaction. It was demonstrated the possibility of glucose determination with the help of proposed reaction in chocolate and fruit juice samples. The limit of detectionwas 7·10-5 mol/l of glucose.
Keywords: -